Spinal metastases from non-small cell lung cancer: Is surgical extent enough by following suggestions of the Tomita and Tokuhashi scores? - Huang, An-Ping; Yang, Ching-Yao; Xiao, Furen; Yang, Shih-Hung; Chen, Chang-Mu; Lai, Dar-Ming; Tsuang, Fon-Yih (Asian journal of surgery, 2024)
The Tomita, revised Tokuhashi and Tokuhashi lung scores are commonly used tools to predict the survival of patients with spinal metastases and to guide decisions regarding surgical treatment. These prognostic scores, however, tend to underestimate the prognosis of patients with lung cancer. We examined surgical outcome and hopefully provide a more accurate reference for management. The consistency between predicted and actual survival was examined using the Tomita and Tokuhashi scores. Various factors that may influence survival were analyzed. Primary outcomes were overall survival (OS) and progression-free survival (PFS), defined as the ambulatory time after the initial surgery. Secondary outcomes included reoperation events, blood loss, and hospitalization days. One hundred seventy-two patients were enrolled. Correct survival predictions were made for 28%, 42%, and 56% with the Tomita, revised Tokuhashi, and Tokuhashi lung scores, respectively. The Tokuhashi lung scores underestimated OS by 35%–40%. Body mass index ≥20, systemic treatment-naïve, good general condition, the use of denosumab, and adenocarcinoma were found to positively affect OS and PFS. There was no significant difference between palliative decompression and excisional surgery regarding OS and PFS. Patients with spinal metastases from lung cancer had better prognosis than that predicted by the Tomita and Tokuhashi scores. Spine surgeons should acknowledge this discrepancy and treat these patients with at least the aggressiveness suggested. Patients with adenocarcinoma, amenable to target therapy, denosumab, good general condition, systemic treatment-naïve are better candidates for surgery. Those with cachexic status and unresectable visceral metastases are worse candidates.